Analisis Penggunaan Diksi dan Gaya Bahasa Beserta Maknanya dalam Lagu “Hormat Kepada Angin” Karya Nadin Amizah - Syifa Nashirah Busra; Khansa Zahria Sabrina; Nuradlin Alisha Binte Mohamad Zainuddin; Nisrina Azka Calista (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Songs that can make the listener feel related to the message in the song lyrics get a lot of attention. The choice of words in song lyrics is important so that listeners can feel and understand the message of the musician both implicitly and explicitly. Language style is also important in song lyrics to add beauty to the delivery of the singer's message. Therefore, this study aims to analyze the use of word choice (diction) and language style in one of the songs by Indonesian musicians, namely Nadin Amizah entitled “Hormat kepada Angin”. This research uses a qualitative approach with the read-and-record method. Based on the results of the study, researchers found the use of diction (denotative, connotative, synonymy, antonymy, and polysemy) and language style in the lyrics of the song “Hormat ke Angin”.